An optimization model design for energy systems planning and management under considering air pollution control in Tangshan City, China. (November 2016) - Zhen, Jiliang; Huang, GuoHe; Li, Wei; Wu, ChuanBao; Liu, Zhengping
Highlights: An interval fuzzy mixed integer programming (IFMIP) model is designed. Uncertainties are presented as both interval values and fuzzy distributions. Air pollution control with various emission-mitigation scenarios is considered. Results could support the sustainable development of society and environment. Abstract: In this study, an interval-parameter fuzzy programming mixed integer programming method (IFMIP) is designed for supporting the planning of energy systems management (ESM) and air pollution mitigation control under multiple uncertainties. The IFMIP-ESM model is based on an integration of interval-parameter programming (IPP), fuzzy programming (FP), and mixed-integer programming (MIP), which can reflect multiple uncertainties presented as both interval values and fuzzy distributions numbers. Moreover, it can successfully identify dynamics of capacity expansion schemes, reflect dual dynamics in terms of interval membership function, and analyze various emission-mitigation scenarios through incorporating energy and environmental policies. The designed model is applied to a case of energy systems management in Tangshan City, China, and the results indicate that reasonable solutions obtained from the model would be helpful for decision makers to effectively (a) adjust the allocation patterns of energy resources and transform the patterns of energy consumption and economic development, (b) facilitate the implement of air pollution control action plan, and (c) analysis dynamic interactions among system cost, energy-supply security, and environmental requirement.